Mineral Industries Of Latin America And Canada ? Introduction (5cc34913-a043-4f5a-a37c-6b63984f0011) - David B. Doan (The National Institute for Occupational Safety and Health (NIOSH), 1995)
This regional report covers 1993 mining and related activity in approximately 40 countries and territories of Canada, Latin America, and the Caribbean Basin. These countries of the Western Hemisphere, as with the United States, are endowed with a great variety of minerals, including metals, industrial minerals, and energy minerals. For most of these countries, such mineral production helps form foundations for their economies and earns export credits including hard currencies. Table 1 depicts an overall view of Latin America and Canada's production of its major mineral commodities in 1993; subsequent tables show the role of Latin America and Canada in world mineral production, trade, and import dependency on minerals from Latin America and Canada by the United States. Overall, the picture emerges of a rich mineral diversity throughout the hemisphere, attracting increasing interest and investment, and complementing the mineral resources of the United States.